Integrating Sustainability Thinking in Science and Engineering Curricula : Innovative Approaches, Methods and Tools - Leal Filho, Walter; Azeiteiro, Ulisses M.; Caeiro, Sandra; Alves, Fátima (World Sustainability Series,, 2015)
Including considerations of sustainability in universities' activities has long since become mainstream. However, there is still much to be done with regard to the full integration of sustainability thinking into science and engineering curricula. Among the problems that hinder progress in this field, the lack of sound information on how to actually implement it is prominent. Created in order to address this need, this book presents a wealth of information on innovative approaches, methods and tools that may be helpful in translating sustainability principles into practice.